Brassinosteroids regulate plasma membrane anion channels in addition to proton pumps during expansion of Arabidopsis thaliana cells - Zhang, Z. (2005)
Brassinosteroids (BRs) are involved in numerous physiological processes associated with plant development and especially with cell expansion. Here we report that two BRs, 28-homobrassinolide (HBL) and its direct precursor 28-homocastasterone (HCS), promote cell expansion of Arabidopsis thaliana suspension cells. We also show that cell expansions induced by HBL and HCS are correlated with the amplitude of the plasma membrane hyperpolarization they elicited. HBL, which promoted the larger cell expansion, also provoked the larger hyperpolarization. We observed that membrane hyperpolarization and cell expansion were partially inhibited by the proton pump inhibitor erythrosin B, suggesting that proton pumps were not the only ion transport system modulated by the two BRs. We used a voltage clamp approach in order to find the other ion transport systems involved in the PM hyperpolarization elicited by HBL and HCS. Interestingly, while anion currents were inhibited by both HBL and HCS, outward rectifying K+ currents were increased by HBL but inhibited by HCS. The different electrophysiological behavior shown by HBL and HCS indicates that small changes in the BR skeleton might be responsible for changes in bioactivity. © 2005 JSPP.